TANGGUNG JAWAB PT. LION MENTARI AIRLINES SEBAGAI PENYEDIA JASA PENERBANGAN KEPADA KONSUMEN AKIBAT ADANYA KETERLAMBATAN ATAU PEMBATALAN JADWAL PENERBANGAN (STUDI KASUS : PUTUSAN NOMOR 641/PDT.G/2011/PN.DPS) - Agung Satrianingsih, Ari; Puspawati, I Gusti Ayu; Rudy, Dewa Gde (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 06, Oktober 2014)
Journal entitled “Liability of PT. Lion Mentari Airlines as flight company toconsumers in flight delayed and cancelation of flight (Case Study: Denpasar’s DistrictCourt decision number: 641/PDT.G/2011/PN.DPS is based oftentimes consumersespecially flight consumers complaint the services was given if there is delayed orcancelation of flight in organizing air freight. So that, important to know how legalliability in practice of Lion Mentari Airlines Company in Denpasar as flight company to consumers about flight delayed and cancelation of flight based on law and throughDenpasar’s District Court decision number : 641/PDT.G/2011/PN.DPS.The writing method that used is the empirical laws. Based on researching result inNgurah Rai International Airport, Lion Mentari Airlines Company always givescompensation caused flight delayed or cancelation of flight to the consumers, but theenforcement of that liability obstructed by services factor. In accordance with theDenpasar’s District Court decision number : 641/PDT.G/2011/PN.DPS, Lion MentariAirlines Company only gives compensation like as drinks and snack and offers ticketrefund, but can’t help flight diversion (to another flight company).
Keywords: Liability, Flight Delayed, Cancelation Of Flight